2016
DOI: 10.3390/toxins8040096
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms that Determine the Differential Stability of Stx+ and Stx− Lysogens

Abstract: Phages 933W, BAA2326, 434, and λ are evolutionarily-related temperate lambdoid phages that infect Escherichia coli. Although these are highly-similar phages, BAA2326 and 933W naturally encode Shiga toxin 2 (Stx+), but phage 434 and λ do not (Stx−). Previous reports suggest that the 933W Stx+ prophage forms less stable lysogens in E. coli than does the Stx− prophages λ, P22, and 434. The higher spontaneous induction frequency of the Stx+ prophage may be correlated with both virulence and dispersion of the Stx2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…If prophage induction successfully highjacks the phage infection during production, then the prophage will be released into the medium, and possibly contaminate the therapeutic preparation that should exclusively contain the lytic phage. Finally, the induction of active prophages can also occur spontaneously with various frequencies [ 44 ], typically one in 10 3 –10 5 cells, but sometimes one in 10 2 cells [ 45 ], and certain toxin-encoding phages were shown to be induced spontaneously with higher frequency than their non-toxin-encoding relatives [ 46 ]. As a consequence, populations of lysogens are typically contaminated with free temperate phages [ 47 ].…”
Section: Prophages In Bacterial Production Strainsmentioning
confidence: 99%
“…If prophage induction successfully highjacks the phage infection during production, then the prophage will be released into the medium, and possibly contaminate the therapeutic preparation that should exclusively contain the lytic phage. Finally, the induction of active prophages can also occur spontaneously with various frequencies [ 44 ], typically one in 10 3 –10 5 cells, but sometimes one in 10 2 cells [ 45 ], and certain toxin-encoding phages were shown to be induced spontaneously with higher frequency than their non-toxin-encoding relatives [ 46 ]. As a consequence, populations of lysogens are typically contaminated with free temperate phages [ 47 ].…”
Section: Prophages In Bacterial Production Strainsmentioning
confidence: 99%
“…Given the central role of the repressor in governing prophage induction, we have been probing the activities of the repressors of Stx-encoding phages and comparing them with that of the repressors from phages that do not encode Stx. In particular, we are examining the Stx 2-encoding prophages 933W [ 25 ] and BAA2326 [ 26 ], both of which undergo spontaneous induction at higher frequencies than do non-Stx-encoding prophages, 434 and λ [ 27 ]. Since the higher spontaneous induction frequencies of these Stx encoding phages are seen both in wild-type E. coli strains and in rec A mutant strains, the observed increased induction frequency of these prophages is at least partially independent of RecA*-stimulated repressor auto-cleavage [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other experiments performed in vitro indicated that some other factors or conditions that might potentially be present (either often or rarely) in the human gut can induce prophages to some extent. They include low pH (<4) ( 38 , 44 ), increased concentrations of sodium chloride (2–3%) ( 45 , 46 ) or bile salts ( 44 ), monovalent cations ( 46 ), chelators of Mg 2+ ions such as EDTA or citrate ( 47 , 48 ), disodium phosphate ( 48 ), copper ( 49 ), and cyanide ( 49 ). There are also reports showing that some physical conditions might also cause prophage induction, for instance irradiation with 60 Co ( 50 ), high hydrostatic pressure ( 51 ) or a 50 Hz rotating magnetic field ( 52 ).…”
Section: Mechanisms Of Prophage Induction In Vitro mentioning
confidence: 99%